Determination of Trace Metals in Engine oil by Direct Sample Introduction Inductively Coupled Plasma Mass Spectrometry - Chuan, Luo; Wu, Beilei; Zhang, Ying (Asian Journal of Chemistry, 2013)
A rapid method was developed for the determination of the vanadium, manganese, nickel, copper, silver, cadmium, tin, barium and lead in engine oil by inductively coupled plasma mass spectrometry (ICP-MS). Direct sample introduction was performed with a special organic sample kit after dilution of the high viscosity engine oil with a suitable organic solvent. The sample up-take rate was optimized be to 50-100 μL/min with a continuous dose of additional O2 (20 %) in the aerosol gas to prevent the deposition of carbon on the sampler and the extinction of plasma by the high viscosity of engine oil. The detection limits were less than 3.18 ng/g. The relative standard deviations were less than 4.9 %. The spiked recoveries were 90.1-101.7 %.